2014
DOI: 10.1021/la5001057
|View full text |Cite
|
Sign up to set email alerts
|

Studying the Influence of Surface Topography on Bacterial Adhesion using Spatially Organized Microtopographic Surface Patterns

Abstract: The influence of surface topography on bacterial adhesion has been investigated using a range of spatially organized microtopographic surface patterns generated on polydimethylsiloxane (PDMS) and three unrelated bacterial strains. The results presented indicate that bacterial cells actively choose their position to settle, differentiating upper and lower areas in all the surface patterns evaluated. Such selective adhesion depends on the cells' size and shape relative to the dimensions of the surface topographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
139
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(152 citation statements)
references
References 52 publications
7
139
0
1
Order By: Relevance
“…Many micrometer-and nanometer-scale topographic patterns with varying shape and size have been shown to inhibit biofilm formation compared to flat surfaces of the same material [29,34]. It was concluded by Perera et al that microtopographic surface patterns represent a promising approach to inhibit bacterial adhesion and biofilm formation, since they found protruding and receding squares, circles, and parallel channels on their material provoked a significant reduction in bacterial adhesion relative to the smooth control samples [35]. Previous study has shown the grit-blasting and hydrofluoric acid etching could create nano-scale topography on zirconia surfaces [26].…”
Section: Discussionmentioning
confidence: 99%
“…Many micrometer-and nanometer-scale topographic patterns with varying shape and size have been shown to inhibit biofilm formation compared to flat surfaces of the same material [29,34]. It was concluded by Perera et al that microtopographic surface patterns represent a promising approach to inhibit bacterial adhesion and biofilm formation, since they found protruding and receding squares, circles, and parallel channels on their material provoked a significant reduction in bacterial adhesion relative to the smooth control samples [35]. Previous study has shown the grit-blasting and hydrofluoric acid etching could create nano-scale topography on zirconia surfaces [26].…”
Section: Discussionmentioning
confidence: 99%
“…Detailed analysis of structural-mechanical properties of the treated surfaces (roughness, fractal and wave properties, elastic modulus) and the cross-sections of the modified layer are given in the work [19]. In particular, the elastic modulus of the surface, determined by the AFM nanoindentation, increases with the plasma energy and fluence and was 20 MPa for the untreated PU, 125 MPa (PIII 1-16), 254 MPa (1-17) and 1900 MPa (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17).…”
Section: Resultsmentioning
confidence: 99%
“…Treatment of soft polymer leads to the formation of a pronounced wrinkled texture on the surface [15], the peculiarities of surface texture affect the antibacterial properties of the coating [16,17]. The wrinkling phenomenon is related with the loss of stability of the hard layer on the soft substrate due to thermal-induced deformation [18].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism preventing protein adsorption to PEG is still not understood in detail, however, the main reason is due to the strong association, through hydrogen bonding, between PEG and water leading to an excluded volume effect making protein adsorption unfavourable [84]. In addition, PEG brushes have been found to provide a steric barrier preventing compounds coming in contact with the surface, preventing adhesion [85]. A issue with the use of PEG is that it is susceptible to oxidation which leads to a reduction in its adsorption resistance over time [86].…”
Section: Hydrophilic Polymersmentioning
confidence: 99%